A Mediterranean-style Eating Pattern Lower in Lean Red Meat Reduced Plasma Trimethylamine N-Oxide in Adults Classified as Overweight or Obese (P08-030-19). (24th October 2019) - Gertz, Erik; Wang, Yu; O'Connor, Lauren; Campbell, Wayne; Bennett, Brian
Abstract: Objectives: To determine the effect of adopting a Mediterranean-style eating pattern with different quantities of lean unprocessed red meat on the plasma concentration of Trimethylamine N-Oxide (TMAO), an emerging potential cardiovascular disease risk factor, in middle-aged adults classified as overweight or obese. Methods: Thirty-nine adults (12 males and 27 females; age 46 ±10 years, BMI 30.6 ± 3.6 kg/m 2 ; mean ± SD) participated in a randomized, crossover and controlled feeding trial. Each participant consumed a Mediterranean-style eating pattern for two 5-week intervention periods separated by ∼4 weeks of consuming their unrestricted, self-selected diet (washout). The Mediterranean-style eating pattern contained either a commonly recommended amount of red meat (∼200 g/wk, Med-200) or the average amount consumed in the U.S. (∼500 g/wk, Med-500). Plasma samples were collected before (baseline) and at the end (post) of the two intervention periods and TMAO was measured by stable isotope dilution chromatography tandem mass spectrometry. Geometric means were compared with mixed model tests in SAS. Results: Baseline TMAO concentrations were not different between interventions (Med-200 = 4.4 ± 2.7 and Med-500 = 5.2 ± 4.5 μM, P = 0.476). These concentrations are similar to values reported in healthy adults. Post-intervention, TMAO was lower in Med-200 vs. Med-500 (3.1 ± 1.2 and 5.0 ± 2.6 μM, P = 0.001). Conclusions: The 2015–2020 Dietary Guidelines for Americans encourages adopting a Mediterranean-style eating pattern to promote cardiovascular health, including reduced blood pressure and improved lipid-lipoprotein profile. The current results suggest that adopting a Mediterranean-study eating pattern may also reduce the cardiovascular disease risk factor TMAO, but only when it contains a lower, recommended, amount of lean unprocessed red meat. The influences of animal- and plant-based foods consumed with a Mediterranean-style and other healthy eating patterns on emerging cardiovascular disease risk factors remain to be determined. This trial was registered at clinicaltrials.gov as NCT02573129. Funding Sources: Supported by theBeef Checkoff, the Pork Checkoff, the NIH pre-doctoral training grant 5T32DK076540-08, the NIH-supported Indiana Clinical and Translational Sciences Institute and the USDA-ARS-Western Human Nutrition Research Center.